2013
DOI: 10.1519/jsc.0b013e318281637b
|View full text |Cite
|
Sign up to set email alerts
|

Relationships Between Rapid Isometric Torque Characteristics and Vertical Jump Performance in Division I Collegiate American Football Players

Abstract: The purpose of the present study was to examine the relationships between absolute and body mass-normalized rapid isometric torque variables and vertical jump (VJ) performance of the leg extensors and flexors in elite National Collegiate Athletic Association Division I Football Bowl Subdivision collegiate American football players. Thirty-one players performed isometric maximal voluntary contractions of the leg extensor and flexor muscle groups and a countermovement VJ. Rate of torque development (RTD) and the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
11
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(12 citation statements)
references
References 36 publications
1
11
0
Order By: Relevance
“…Previous studies have used correlation coefficients rather than stepwise regressions to assess the rate of torque development-jump height relationship and so were not affected by this issue (De Ruiter et al, 2006;Marcora & Miller, 2000;McLellan et al, 2011;Thompson et al, 2013;Tillin et al, 2013). These assertions are further supported by a significant correlation between peak isometric torque and RTD 100-150 (r = 0.546; P = 0.01) in the present study.…”
Section: Discussionsupporting
confidence: 79%
See 1 more Smart Citation
“…Previous studies have used correlation coefficients rather than stepwise regressions to assess the rate of torque development-jump height relationship and so were not affected by this issue (De Ruiter et al, 2006;Marcora & Miller, 2000;McLellan et al, 2011;Thompson et al, 2013;Tillin et al, 2013). These assertions are further supported by a significant correlation between peak isometric torque and RTD 100-150 (r = 0.546; P = 0.01) in the present study.…”
Section: Discussionsupporting
confidence: 79%
“…However, further research is needed to explain quantitatively the relative contributions of kinetic and kinematic variables to this movement. Of the kinetic determinants, greater rate of force or torque development has frequently been associated with increased CMJ performance (De Ruiter, van Leeuwen, Heijblom, Bobbert, & De Haan, 2006;Marcora & Miller, 2000;McLellan, Lovell, & Gass, 2011;Thompson et al, 2013). Both rate of force development and rate of torque development measure the capabilities of skeletal muscle to rapidly generate muscle forces and for the purposes of the present study will be referred to as rate of torque development.…”
Section: Introductionmentioning
confidence: 98%
“…). In a majority of these studies (Hakkinen et al., ; Aagaard et al., ; Suetta et al., ; Bojsen‐Moller et al., ; Caserotti et al., ; Thorlund et al., ; Dewhurst et al., ; Thompson et al., , ; Waugh et al., , ; Haff et al., ), absolute RFD was derived as the average slope of the force–time curve over specified time intervals of 0–30, 0–50, 0–100, 0–200 and even 0–400 ms relative to the onset of contraction, whereas MRFD typically has been quantified as the peak slope of the force–time curve (Gorostiaga et al., ; Sahaly et al., ; Aagaard et al., ; Mirkov et al., ; Suetta et al., ; Bojsen‐Moller et al., ; Korhonen et al., ; Holtermann et al., ; Hartmann et al., ; Almosnino et al., ; Thompson et al., , ; Haff et al., ). RFD has also been calculated as the time taken from the beginning of force production to the attainment of different fractions (e.g.…”
Section: Methodological Considerations In Rate Of Force Development Amentioning
confidence: 99%
“…Isometric explosiveness, or the rate of torque development (RTD) in isometric contractions, has been examined in relation to jump performance in adults, with inconsistent results. While several studies reported significant correlations between jump performance and knee-extensor RTD (de Ruiter et al 2010;de Ruiter et al 2006;Paasuke et al 2001;Thompson et al 2013), others did not (Baker et al 1994;McGuigan and Winchester 2008). This inconsistency may be due to methodological differences between studies, such as different testing modalities, contraction types, or joint angles, or to different populations (e.g., athletes and non-athletes).…”
Section: R a F T Introductionmentioning
confidence: 98%